The Internal Auditor Psychological Factors Facing Organizational Changes - Indrawati Yuhertiana; Gideon SB; Corry Natasha Patrioty (Nusantara Science and Technology Proceedings)
This study aims to justify the psychological factors of internal auditor related with the organizational changes. An exploratory research was done to describe the perception of internal auditor in Government State Owned company by fill in the questionnaire that measure their psychology factor facing the change in organization. There are find 140 respondent but only 37 auditor. The result of this study find that psychology factor measured by the cognitive, affective and behavioral indicators. In cognitive basis, respondents do not feel bothered by the change. Respondents want and are willing to do new things and do not resist new ideas. In affective respondents assume and are confident that the changes the organization benefit. The change was beneficial, useful, wonderful as it can be free to new ideas. In Behavioral tendency, seen a statement on the level of agree to behave are trying new ideas, using new approaches and supporting change.